New insights into the interplay between autophagy and oxidative and endoplasmic reticulum stress in neuronal cell death and survival - Gao, Yahao; Wang, Changshui; Jiang, Di; An, Gang; Jin, Feng; Zhang, Junchen; Han, Guangkui; Cui, Changmeng; Jiang, Pei (Frontiers in Cell and Developmental Biology, 2022)
Autophagy is a dynamic process that maintains the normal homeostasis of cells by digesting and degrading aging proteins and damaged organelles. The effect of autophagy on neural tissue is still matter of debate. Some authors suggest that autophagy has a protective effect on nerve cells, whereas others suggest that autophagy also induces the death of nerve cells and aggravates nerve injury. In mammals, oxidative stress, autophagy and endoplasmic reticulum stress (ERS) constitute important defense mechanisms to help cells adapt to and survive the stress conditions caused by physiological and pathological stimuli. Under many pathophysiological conditions, oxidative stress, autophagy and ERS are integrated and amplified in cells to promote the progress of diseases. Over the past few decades, oxidative stress, autophagy and ERS and their interactions have been a hot topic in biomedical research. In this review, we summarize recent advances in understanding the interactions between oxidative stress, autophagy and ERS in neuronal cell death and survival.